An incipient public authority: A short pre-history of the Central Bank of Iceland - Helgi Skúli Kjartansson (Icelandic Review of Politics & Administration, 2011)
The author surveys the central banking functions progressively assumed by the National Bank of Iceland (Landsbanki Íslands) prior to the establishment in 1961 of the separate Icelandic Central Bank (Seðlabanki Íslands). The NBI took over the issuance of banknotes in 1924; its central banking functions were defined by law (unrealistically, as the law foresaw a functioning gold standard which never was put into practice) in 1927; its central banking section became financially separate in 1930; it was put under separate administration by law in 1957, and given the right, first exercised in 1960 onwards, to determine interest rates and reserve requirement in commercial banking. Among the particular points under discussion are NBI´s responsibility for other banks (none whatsoever when the country´s second bank failed in 1930); its involvement, from the early 1930s onward, in a regime of currency controls; its control of interest rates (limited and largely by persuasion as its rediscount rate was not an instrument of monetary policy); and its increasing willingness to state its own its monetary policy, even in opposition to the policy pursued by national government.